Implementation of Scaffolding Learning Strategy in Learning - Riza Ashari; Tiara Eki Wahyu Rinawati (Yayasan Letiges Konsultan Sosial, 2024)
This study aims to describe the application of scaffolding learning strategies in Fiqh material for Class 3F at the Modern Islamic Boarding School Darussalam Gontor for Girls Campus 2 which is expected to improve Student Activity and Learning Outcomes. This study is a classroom action research. Data collection instruments use interview sheets, observation sheets, field notations, and exam questions. The analysis adopts the Kemmis & Mc Taggart model, with two cycles, each consisting of planning, action, observation and reflection, which are carried out in two cycles to determine student activity and learning outcomes. The results of this study indicate that in cycle I student activity reached 53% and in cycle II student learning activity reached 94%. The application of scaffolding learning strategies can improve female students' learning outcomes in Fiqh subjects in cycle I with learning achievements of 53%, in cycle II reaching a learning outcome percentage of 100%. Scaffolding strategies can improve students' learning activity. It can be seen from the following Activity indicators such as involvement in problem-solving, resilience in joint discussions, courage in expressing opinions, and increased use of strategies in learning.